The impact of pregnancy rates of using two different cut-off levels for high serum estradiol levels on the day of the hCG injection: Results from the same cohort of patients with long down-regulated ART cycles [Ayni{dotless} yüt hasta kohortunda hcg günü oluşturulan iki farkli{dotless} serum östradiol eşik deǧerlerinin yüt gebelikleri üzerine etkileri] - (:unkn) unknown (My University, 2013)
Objective: To determine, from a single cohort of patients whether on the day of the human chorionic gonadotropin (hCG) injection, two different cut-off levels for high serum estradiol (E2) levels affect pregnancy rates in long-down regulated assisted reproductive technology (ART) cycles. Patients and Methods: A retrospective cohort analysis was performed in a University affliated hospital on 539 women undergoing consecutive in vitro fertilization/intacytoplasmic sperm injection (IVF/ICSI) treatment with long-down regulation and recombinant follicular stimulating hormone (FSH) injections. The cut-off level for high E2 concentration was calculated according to a centile analysis of E2 levels on the day of hCG administration. Women in group 1 were divided into subgroup A with E2 levels from the 25th to 75th centiles (1040-2500pg/ml) and subgroup B with E2 levels from the 75th to 100th centiles (>2500pg/ml), respectively. Women in group 2 were divided into subgroup A with E2 levels from the 10th to 90th centile (650-3100pg/ml) and subgroup B with E2 levels from the 90th to 100th centile (>3100pg/ml), respectively. The clinical pregnancy rates and ongoing pregnancy rates were compared. Results: The clinical pregnancy rates and ongoing pregnancy rates were similar in group 1 and group 2. Conclusion: High serum E2 levels on the day of the hCG injection day either set at 75th (2500pg/ml) or 90th percentiles (3100pg/ml) do not compromise pregnancy rates in cycles down-regulated with gonadotropin-releasing hormone (GnRH) analogues.
Keywords: Estradiol; Gonadotropin-releasing analogue; Human chorionic gonadotropin; Long analogue cycle; Pregnancy